Understanding Canoe Making as a Process of Preserving Cultural Heritage - Peterson, Debora; Hanazaki, Natalia; Li, Fabiana (Ethnobiology Letters, 2019)
Canoes are deeply ingrained elements of the Caiçara culture, not only for their historical and current practical uses, but also for their socio-cultural outcomes. Caiçara people are the descendants of Europeans, Africans, and Indigenous peoples who inhabit parts of the Atlantic Forest in the southern and southeastern coast of Brazil. Despite this, canoe making has been declining in several Caiçara communities, while many ongoing initiatives have attempted to encourage the maintenance of this practice. This article explores some of the Caiçara-canoe relationships within the Juatinga Ecological Reserve, in southeastern Brazil. We discuss how canoes are an appropriate technology for some fishing techniques, and are thus not easily replaced by fiberglass or aluminum boats. We also explore some socio-cultural dimensions of canoe making in light of the relationships of Caiçara canoe makers and fishers with the forest and with other community members. This article contributes to a growing body of knowledge to protect elements of Caiçara identity, including initiatives to help maintain canoes, canoe making, and the people involved with them.